Short Communication: Ant (Hymenoptera: Formicidae) diversity as bioindicator of agroecosystem health in northern slope of Mount Slamet, Central Java, Indonesia - IMAM WIDHIONO; RIZKITA DINDA PANDHANI; DARSONO DARSONO; EDI RIWIDIHARSO; SLAMET SANTOSO; LUCKY PRAYOGA (Biodiversitas Journal of Biological Diversity, 2017)
Widhiono I, Pandhani RD, Darsono, Riwidiharso E, Santoso S, Prayoga L. 2017. Short Communication: Ant (Hymenoptera: Formicidae) diversity as bioindicator of agroecosystem health in northern slope of Mount Slamet, Central Java, Indonesia. Biodiversitas 18: 1475-1480. This study examined the diversity of ant assemblages in two different agroecosystems (organic and intensive farming) with maize as main crops on the northern slope of Mount Slamet, Indonesia from April to August 2015. The response of ant diversity to the different farming systems was evaluated. In total, 359 ants from 17 species in five subfamilies were collected: 13 species from the organic farm and 10 species from the conventional farm. Seven (41%) species were found only on the organic farm, four (23%) species were found only on the conventional farm, and six (35%) species were found on both. The Morisita-Horn similarity index (33%) showed that the similarity of the species composition in the two habitats was low. More individual ants were found on the organic farm than the intensive farm [287 (79.94%) vs. 72 (20.05%) individuals]. The diversity of the ants was affected by the density of weeds with organic farming. Hypoponera sp. had the highest Indicator Value (50.7), followed by Aphaenogaster sp. (28.9), Diacamma sp. (28.2), and Odontoponera sp. (27.6), however only Odontoponera sp can be used as bioindicator. Although the ant diversity was higher with organic farming than with intensive farming, there was no correlation with soil conditions. As a bioindicator, the Indicator Value reflects agroecosystem health better than does ant diversity.